In vivo research of choroidal neovascularization – an animal model - Jasielska, Monika; Mackiewicz, Jerzy; Bieliński, Paweł (Polish Journal of Public Health, 2010)
Introduction. Choroidal neovascularization (CNV) is a vascular hyperplasia of vessels, originating from choroid capillary vessels which, through the Bruch’s membrane, get into the area under the retinal pigment epithelium as well as the retinal pigment epithelium and the retinal photoreceptors’ region. CNV is known to be the main reason for a severe visual loss in patients with age-related macular degeneration (AMD). AMD is the leading cause of blindness in people over 50 years of age in the western world. Aim. Evaluation of the applicability of a laser-induced mouse model of CNV to investigate the choroidal neovascularization. Material and methods. The research was carried out on C57/BL6 mice. The mice were subjected to laser photocoagulation and two weeks later fluorescein angiography was performed. Results. Two weeks after the laser photocoagulation of the area of pathological fluorescein, a leakage, resembling CNV formation, appeared, after fluorescein injection, in the angiograms of the early (1-3 min) and the late (6-8 min) phase. In the place of the laser spots, a process of formation of large and diffused areas of leakage was observed. These lesions presented an increase in size and intensity during angiography. Conclusions. The laser-induced mouse model of CNV resembles human CNV lesions. The obtained animal model of CNV could be used in further research on CNV which is responsible for the severe visual loss and the damage of retina in age-related macular degeneration.